Dietary Concentrate-to-Forage Ratio Affects Rumen Bacterial Community Composition and Metabolome of Yaks - Yi, Simeng; Dai, Dongwen; Wu, Hao; Chai, Shatuo; Liu, Shujie; Meng, Qingxiang; Zhou, Zhenming (Frontiers in Nutrition, 2022)
Changes in dietary composition affect the rumen microbiota in ruminants. However, information on the effects of dietary concentrate-to-forage ratio changes on yak rumen bacteria and metabolites is limited. This study characterized the effect of three different dietary concentrate-to-forage ratios (50:50, C50 group; 65:35, C65 group; 80:20, C80 group) on yak rumen fluid microbiota and metabolites using 16S rRNA gene sequencing and liquid chromatography-mass spectrometry (LC-MS) analyses. Rumen fermentation parameters and the abundance of rumen bacteria were affected by changes in the dietary concentrate-to-forage ratio, and there was a strong correlation between them. At the genus level, higher relative abundances of norank_f__F082, NK4A214_group, Lachnospiraceae_NK3A20_group, Acetitomaculum, and norank_f__norank_o__Clostridia_UCG-014 were observed with a high dietary concentrate-to-forage ratio (P < 0.05). Combined metabolomic and enrichment analyses showed that changes in the dietary concentrate-to-forage ratio significantly affected rumen metabolites related to amino acid metabolism, protein digestion and absorption, carbohydrate metabolism, lipid metabolism, and purine metabolism. Compared with the C50 group, 3-methylindole, pantothenic acid, D-pantothenic acid, and 20-hydroxy-leukotriene E4 were downregulated in the C65 group, while spermine and ribose 1-phosphate were upregulated. Compared to the C50 group, Xanthurenic acid, tyramine, ascorbic acid, D-glucuronic acid, 6-keto-prostaglandin F1a, lipoxin B4, and deoxyadenosine monophosphate were upregulated in the C80 group, while 3-methylindole and 20-hydroxy-leukotriene E4 were downregulated. All metabolites (Xanthurenic acid, L-Valine, N-Acetyl-L-glutamate 5-semialdehyde, N-Acetyl-L-glutamic acid, Tyramine, 6-Keto-prostaglandin F1a, Lipoxin B4, Xanthosine, Thymine, Deoxyinosine, and Uric acid) were upregulated in the C80 group compared with the C65 group. Correlation analysis of microorganisms and metabolites provided new insights into the function of rumen bacteria, as well as a theoretical basis for formulating more scientifically appropriate feeding strategies for yak.